PERBANDINGAN JUMLAH BAKTERI TANAH PADA HUTAN BERDAUN LEBAR DAN HUTAN BERDAUN JARUM PADA KEDALAMAN TANAH YANG BERBEDA - Abi Gael Sidon; Wahyu Harso; Umrah Umrah; Orryani Lambui (Biocelebes, 2023)
The number of soil microorganisms that play a role in the organic matter decomposition process can be affected by litter quantity and quality. Lignin content is higher in needleleaf than in broadleaf. The study aimed to determine the number of bacteria found in the broadleaf forest and needleleaf forest soil at different soil depths. The soil was collected at depths of 0-5 cm, 10-15 cm, and 20-25 cm at a distance of 1.5 m from the canopy of both broadleaf and coniferous forests where their locations are close. The results showed that the soil organic matter of broadleaf forests was higher than needleleaf forests, especially at depths of 0-5 cm and 10-15 cm. The number of bacteria on broadleaf forest soil is higher than on needleleaf forest soil, especially at 0-5 cm depth. The organic matter in both forest soils decreases with the soil depth. A positive correlation is obtained between the quantity of organic matter and the number of bacteria. The quantity and quality of organic matter in the soil will affect the number of bacteria.